Pembentukan Karakter bagi Anak Usia Dini di Lingkungan Sekolah dan Masyarakat - Farantika, Dessy; Hidayah, Choirul; Rachmah, Laela Lutfiana (Journal of Childhood Education, Development and Parenting, 2023)
Character formation for early childhood is something urgent that must be done by the family, school, and community. Without the involvement of all parties, character formation cannot get maximum results. This descriptive qualitative research with literature study discusses the formation of character in early childhood in the school and community environment. The data analysis technique is using content analysis by sorting out data according to the objectives and research problems. This paper produces the following conclusions. First, the formation of character in early childhood in the school environment is largely determined by teachers who act as evaluators, motivators, counselors, mentors, educators, role models, development designers, consultants, and mediators. Second, the formation of character in early childhood in the community must pay attention to several challenges as follows, among others: the negative impact of television, the negative impact of promiscuity, the negative impact of the internet, the negative impact of karaoke places, the negative impact of gadgets and smartphones that are not controlled by parents, and the adverse effects of tourist attractions. In addition, character education should be carried out in a conducive environment. Character education needs to be carefully planned by stakeholders, such as think tanks, both from character experts (morals) such as clergy (religious leaders), non-formal leaders (community leaders), school principals, teachers, parents, and others.